Design of Structural Parameters of Cutters for Tea Harvest Based on Biomimetic Methodology - Zhe Du; Yongguang Hu; Yongzong Lu; Jing Pang; Xinping Li (Applied Bionics and Biomechanics)
Owing to their sharp teeth, crickets can eat through new shoots of the stalks of tea plants. Inspired by the special geometrical structure of the teeth of crickets, this study designed a biomimetic cutter to reduce the force and energy required to cut the stalks of tea plants. Therefore, four biomimetic cutters were considered: a, b, c, and d. Cutter a was a traditional cutter used for comparison with the other three cutters, which were biomimetic. The cutters were manufactured using 3D printing technology and assessed by a texture tester at different loading speeds (5, 10, and 15 mm/s, respectively). The results show that cutter c delivered better performance compared to cutter a at loading speeds of 5, 10, and 15 mm/s, respectively. However, at 15 mm/s loading speed, the maximum cutting forces required for cutters b and c were 9.43% and 6.04% lower, respectively, than that for cutter a (9.021 N). Similarly, the energies consumed by cutters b and c were 13.8% and 4.24% lower than that consumed by cutter a (1.225 J). In addition, cutter c delivered the best results compared to others. Based on the study results, it was concluded that the biomimetic cutters can thus help to optimize the tea harvest.